1978
DOI: 10.1007/bf00157275
|View full text |Cite
|
Sign up to set email alerts
|

Solar Heii(304 �) and Si xi(303 �) line profiles

Abstract: Additional observations of He II (304 &) and Si xI (303 ~) were obtained from a high resolution rocket spectrograph flown on 30 August, 1973 and 20 January, 1975. The profile of the He ri (304 ~) line is everywhere clearly non-gaussian across the solar disk, except in bright active areas. Near the limb, the profile is distinctly reversed. The profile of the Si xr (303 *) line is essentially gaussian for all regions across the solar disk. Measurements of the He II/Si xr intensity ratio indicate that the average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 7 publications
3
7
0
Order By: Relevance
“…7 in ). The linewidth (FWHM ≃ 0.08 Å) is somewhat smaller than the value of 0.10 Å observed by Doschek et al (1974) and Cushman & Rense (1978), but is very similar to that computed by Fontenla et al (1993). Fontenla et al (2002) predict greater widths if significant flows are present.…”
Section: Results Using Maxwellian Collision Ratessupporting
confidence: 70%
“…7 in ). The linewidth (FWHM ≃ 0.08 Å) is somewhat smaller than the value of 0.10 Å observed by Doschek et al (1974) and Cushman & Rense (1978), but is very similar to that computed by Fontenla et al (1993). Fontenla et al (2002) predict greater widths if significant flows are present.…”
Section: Results Using Maxwellian Collision Ratessupporting
confidence: 70%
“…This figure also indicates the main contributors to this relatively broad-band channel: the closely spaced Si xi line at 303.3Å and He ii line at 303.8Å. Contribution of the Si xi line has been previously investigated by several authors, who have found it to be around 3-4% for the on-disk quiet Sun regions and more than 90% for the coronal emission (Cushman and Rense, 1978;Thompson and Brekke, 2000). Since plasma conditions in prominences are similar to that of the quiet Sun, helium emission is typically dominant in them.…”
Section: Observationsmentioning
confidence: 58%
“…Let us recall that this line corresponds to the 1s 2 1 S-1s2p 1 P 0 transition of parahelium. It has been measured in the solar chromosphere with different techniques (Dupree & Reeves 1971;Dupree et al 1973;Delaboudinière & Crifo 1976;Cushman & Rense 1978). The chromospheric profiles (Cushman & Rense 1978) were rather broad and even possibly self-reversed (1976).…”
Section: Some Features Of the 58433å Hei Linementioning
confidence: 99%